Risk of Incident Diabetes Mellitus, Weight Gain, and Their Relationships With Integrase Inhibitor–Based Initial Antiretroviral Therapy Among Persons With Human Immunodeficiency Virus in the United States and Canada. (16th September 2020) - Rebeiro, Peter F; Jenkins, Cathy A; Bian, Aihua; Lake, Jordan E; Bourgi, Kassem; Moore, Richard D; Horberg, Michael A; Matthews, W Christopher; Silverberg, Michael J; Thorne, Jennifer; Mayor, Angel M; Lima, Viviane D; et al.
Abstract: Background: Integrase strand transfer inhibitor (INSTI)–based combination antiretroviral therapy (cART) is associated with greater weight gain among persons with human immunodeficiency virus (HIV), though metabolic consequences, such as diabetes mellitus (DM), are unclear. We examined the impact of initial cART regimen and weight on incident DM in a large North American HIV cohort (NA-ACCORD). Methods: cART-naive adults (≥18 years) initiating INSTI-, protease inhibitor (PI)–, or nonnucleoside reverse transcriptase inhibitor (NNRTI)–based regimens from January 2007 through December 2017 who had weight measured 12 (±6) months after treatment initiation contributed time until clinical DM, virologic failure, cART regimen switch, administrative close, death, or loss to follow-up. Multivariable Cox regression yielded adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for incident DM by cART class. Mediation analyses, with 12-month weight as mediator, similarly adjusted for all covariates. Results: Among 22 884 eligible individuals, 47% started NNRTI-, 30% PI-, and 23% INSTI-based cART with median follow-up of 3.0, 2.3, and 1.6 years, respectively. Overall, 722 (3%) developed DM. Persons starting INSTIs vs NNRTIs had incident DM risk (HR, 1.17 [95% CI, .92–1.48]), similar to PI vs NNRTI initiators (HR, 1.27 [95% CI, 1.07–1.51]). This effect was most pronounced for raltegravir (HR, 1.42 [95% CI, 1.06–1.91]) vs NNRTI initiators. The INSTI–DM association was attenuated (HR, 1.03 [95% CI, .71–1.49] vs NNRTIs) when accounting for 12-month weight. Conclusions: Initiating first cART regimens with INSTIs or PIs vs NNRTIs may confer greater risk of DM, likely mediated through weight gain. Abstract : People with human immunodeficiency virus initiating combination antiretroviral therapy with a protease inhibitor– or integrase strand transfer inhibitor–containing regimen, particularly raltegravir, should be monitored for incident diabetes mellitus, as their risk is elevated relative to nonnucleoside reverse transcriptase initiators. This increased risk is not entirely explained by weight gain.